Pemanfaatan Koperasi Simpan Pinjam Politeknik Negeri Batam Melalui Web - Afdhol Dzikri; Meyti Eka A (JURNAL INTEGRASI, 2013)
The use of manual systems in the credit application process at Credit Unions Batam Polytechnic still cause a lot of problems that can hinder the performance part that handles credit application process. The employee who has been a member for this is the difficulty in getting information about the number of installments that have been paid and the remaining unpaid. And on the part of the manager who was represented by the Assistant Director II have not been able to get information quickly on a monthly and annual reports. Therefore, developed an application to automate the process of loan application at the Polytechnic Cooperative to better facilitate users due process carried out more effectively and efficiently. Expected to made this application in form filling and submission of member credit, credit reports, and simulation is done manually anymore. This research is an application that helps in filling loan application form, provide a more secure storage of data and can provide online credit card installments.